1991
DOI: 10.1159/000468890
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Radioimmunoassay for Human Group-II Phospholipase A2 and Demonstration of Postoperative Elevation

Abstract: A radioimmunoassay (RIA) for the determination of human group-II phospholipase A(2) (M-PLA(2)) has been developed. M-PLA(2) was purified from human spleen. Monoclonal antibody (IgG) was prepared by fusion of splenic cells from immunized mice with M-PLA(2) and the mouse myeloma cell line NS-1. The RIA was carried out by a single antibody method. The assay is sensitive (0.78 μg/1), reproducible and specific. In healthy individuals, the serum M-PLA2 concentration ranges from 1.4 to 4.2 μg/l, the average being 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 8 publications
0
33
1
Order By: Relevance
“…M-PLA2 concentration was measured by a radioimmunoassay using anti-M-PLA2 monoclonal antibody as described by Matsuda et al (1991). There is no cross-reactivity of this antibody with human P-PLA2, pancreatic trypsin, chymotrypsin, elastase 1 and pancreatic secretory trypsin inhibitor (Matsuda et al, 1991).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…M-PLA2 concentration was measured by a radioimmunoassay using anti-M-PLA2 monoclonal antibody as described by Matsuda et al (1991). There is no cross-reactivity of this antibody with human P-PLA2, pancreatic trypsin, chymotrypsin, elastase 1 and pancreatic secretory trypsin inhibitor (Matsuda et al, 1991).…”
Section: Patientsmentioning
confidence: 99%
“…M-PLA2 concentration was measured by a radioimmunoassay using anti-M-PLA2 monoclonal antibody as described by Matsuda et al (1991). There is no cross-reactivity of this antibody with human P-PLA2, pancreatic trypsin, chymotrypsin, elastase 1 and pancreatic secretory trypsin inhibitor (Matsuda et al, 1991). The purified M-PLA2 was iodinated with [125I]sodium iodide (New England Nuclear, Boston, MA, USA) by the chloramine-T method (Hunter & Greenwood, 1962), and the 251I-labelled M-PLA2 was purified by gel filtration on a PD-10 column (Pharmacia Fine Chemicals, Sweden).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group PLA2-II concentration is increases in serum after extensive surgery and decreasing gradually thereafter. Postoperative group II PLA2 values correlate well with the concentration of Creactive protein in serum [8]. Zieve and Vogel firstly reported that increased PLA2 activity in serum in acute pancreatitis patients in 1961 [8].…”
Section: Role Of Pla2 In Inflammationmentioning
confidence: 88%
“…Postoperative group II PLA2 values correlate well with the concentration of Creactive protein in serum [8]. Zieve and Vogel firstly reported that increased PLA2 activity in serum in acute pancreatitis patients in 1961 [8]. The elevation of PLA2 was correlated with the severity of the disease [9,10].…”
Section: Role Of Pla2 In Inflammationmentioning
confidence: 99%